2007
DOI: 10.1007/s10236-007-0125-2
|View full text |Cite
|
Sign up to set email alerts
|

Downscaling a twentieth century global climate simulation to the North Sea

Abstract: The regional ocean model system (ROMS) is used to downscale a 26-year period of the twentieth century 20C3M experiment from the global coupled Bergen climate model (BCM) for the North Sea. Compared to an observational-based climatology, BCM have good results on the mean temperature, except for too low winter temperature. This is connected to a too weak inflow of Atlantic water. The downscaling gives added value to the BCM results by providing regional details, doubling the Atlantic inflow, and improving the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 22 publications
2
14
1
Order By: Relevance
“…In general, coarse resolution global models cannot capture the current along the Norwegian Trench very accurately, because the horizontal resolution is usually not sufficient to represent the related dynamics. In our downscaling experiments, the ESC and NCC both decrease by Â10%, in contrast to the conclusion of Å dlandsvik and Bentsen (2007). This is probably caused by the fact that the northern boundary in our model is further south than in Å dlandsvik and Bentsen (2007), and it is shown that nesting experiments with different locations of open boundaries could produce different results.…”
Section: Circulation Differences Between Both Modelscontrasting
confidence: 77%
See 1 more Smart Citation
“…In general, coarse resolution global models cannot capture the current along the Norwegian Trench very accurately, because the horizontal resolution is usually not sufficient to represent the related dynamics. In our downscaling experiments, the ESC and NCC both decrease by Â10%, in contrast to the conclusion of Å dlandsvik and Bentsen (2007). This is probably caused by the fact that the northern boundary in our model is further south than in Å dlandsvik and Bentsen (2007), and it is shown that nesting experiments with different locations of open boundaries could produce different results.…”
Section: Circulation Differences Between Both Modelscontrasting
confidence: 77%
“…This method leads to discussion about the choice of open boundary conditions (Palma and Matano, 1998;Marchesiello et al, 2001;Chen et al, 2013). Å dlandsvik and Bentsen (2007) performed the marine downscaling of global simulations to the North Sea from a coupled climate model (20C3M experiment). They reported that the added value of downscaling is to provide the regional details, doubling the *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…The higher-resolution ocean model can then properly represent the roles of topography, tidal mixing, and fronts to produce a realistic ocean circulation. A similar effort has previously been performed for another shelf area, the North Sea (Ådlandsvik and Bentsen 2007).…”
Section: Introductionmentioning
confidence: 93%
“…Ådlandsvik and Bentsen 2007). Moreover, GCMs and ESMs are not optimised for shelf sea hydrodynamics and biogeochemistry, and some key processes relevant to North Sea dynamics, such as tides and physical and biogeochemical coupling at the sediment-water interface, are typically neglected.…”
Section: Introductionmentioning
confidence: 99%